Effect of Rashba spin–orbit interaction on the ground state energy of a D0 centre in a GaAs quantum dot with Gaussian confinement. (December 2015) - Kumar, D. Sanjeev; Boda, Aalu; Mukhopadhyay, Soma; Chatterjee, Ashok
Abstract: The ground state energy of a neutral hydrogenic donor impurity ( D 0 ) trapped in a three-dimensional GaAs quantum dot with Gaussian confinement is calculated in the presence of Rashba spin–orbit interaction. The effect of the spin–orbit interaction is incorporated by performing a unitary transformation and retaining terms up to quadratic in the spin–orbit interaction coefficient. For the resulting Hamiltonian, the Rayleigh-Ritz variational method is employed with a simple wave function within the framework of effective-mass envelope function theory to determine the ground state energy and the binding energy of the donor complex. The results show that the Rashba spin–orbit interaction reduces the total GS energy of the donor impurity. Highlights: Effect of Rashba coupling on a D 0 complex in a GaAs quantum dot is studied. Ground state (GS) energy is shown to decrease with increasing Rashba interaction. GS binding energy, however, turns out be independent of the spin-orbit interaction. Donor electron distribution is also obtained as a function of the dot size.